2023
DOI: 10.38212/2224-6614.3454
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of curcumin and its related substances in turmeric: From raw material selection to application strategies

Abstract: Turmeric ( Curcuma longa L.) is a medicinal plant used extensively in Chinese and Indian traditional medicine as a home remedy for various diseases. It has been used for medical purposes for centuries. Today, turmeric has become one of the most popular medicinal herbs, spices, and functional supplements worldwide. Curcuminoids are linear diary-lheptanoids from the rhizomes that include curcumin and two related compounds: demethoxycurcumin and bisdemethoxycurcumin, which are the active co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 186 publications
(220 reference statements)
0
9
0
Order By: Relevance
“…Beyond its culinary use, turmeric has historically been used in Chinese and Indian traditional medicine for treating various diseases and conditions. Curcumin-a polyphenol and the active component of turmeric-has been extensively studied in recent decades, demonstrating its potential antioxidant, anti-inflammatory, anti-diabetes, and anticancer effects [114]. A systematic review and meta-analysis of 64 RCTs found that turmeric/curcumin supplementation was effective in improving blood levels of TC, TG, LDL-c, and HDL-c [115].…”
Section: Polyphenol-rich Plant Foodsmentioning
confidence: 99%
“…Beyond its culinary use, turmeric has historically been used in Chinese and Indian traditional medicine for treating various diseases and conditions. Curcumin-a polyphenol and the active component of turmeric-has been extensively studied in recent decades, demonstrating its potential antioxidant, anti-inflammatory, anti-diabetes, and anticancer effects [114]. A systematic review and meta-analysis of 64 RCTs found that turmeric/curcumin supplementation was effective in improving blood levels of TC, TG, LDL-c, and HDL-c [115].…”
Section: Polyphenol-rich Plant Foodsmentioning
confidence: 99%
“…2 It has a wide range of applications apart from dietary supplements, namely, in the food industry (colorant and preservative), cosmetics manufacturing, 13 and textile manufacturing (dyeing). 14 However, curcumin's limited absorption in the stomach leads to nonsignificant levels in the bloodstream which affects its wide usage as a lead compound. 15 This is because of its poor oral bioavailability, poor solubility, and hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…It also acts as an immune modulator, metabolism regulator, neuroprotector, and tissue protector . It has a wide range of applications apart from dietary supplements, namely, in the food industry (colorant and preservative), cosmetics manufacturing, and textile manufacturing (dyeing) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel therapeutic agent GZ17-6.02 (602) is comprised of three synthetically manufactured natural compounds in the following ratio: isovanillin (77%), harmine (13%) and curcumin (10%) [ 11 ]. Curcumin as a single agent has low solubility in water, has very poor PK/PD in vivo and failed in the clinic as an anti-cancer agent [ 12 , 13 ]. In our prior in vitro studies using low physiologic concentrations of curcumin, the generation of reactive oxygen species played an important role in the process by which tumor cells were killed [ 14 ].…”
Section: Introductionmentioning
confidence: 99%